EFFECTIVENESS OF STRYCHNINE BUSH EXTRACT (STRYCHNOS LIGUSTRINA BLUME) AGAINST TO PREVALENCE AND SURVIVAL RATE OF DUMBO CATFISH (CLARIAS GARIEPINUS) INFECTED WITH AEROMONAS HYDROPHILA - Zubaidah, Anis; Samsundari, Sri; Hidayaturrahmi, Hidayaturrahmi (xxxx-xxxx)
One of the problemsofintensive catfish culture is the attack of Motile Aeromonas Septicemia disease caused by Aeromonas hydrophila bacteria. To prevent it is necessary to prevent the use of natural antibiotics that is strychnine bush extract. The purpose of this research is to know the ability of strychnine bush extract (Strychnos ligustrina Blume) using methanol solvent in inhibiting the growth of Aeromonas hydrophila bacteria and its effect on prevalence and survival rate in Dumbo catfish (Clarias gariepinus). The method used in this research is the exsperimen method by using complete randomized design (RAL). In this study there were five treatments with different doses of treatment (P1: 6%), (P2: 12%), (P3: 18%), (P4: 24%) and (P5: 30%), each treatment was repeated three replications. Furthermore, the data were analyzed using ANAVA and continued with LSD test. The results showed that the giving of strychnine bush extract with different concentrations had a very significant effect on the width of the Aeromonas hydrophila bacterial resistance zone. The lowest inhibition of the treatment (P1: 6%) with a resistance of 1.79 mm. While the highest inhibition of treatment (P5: 30%) with 8.29 mm inhibition power. In prevalenceofdumbo catfish with givingofsongga extract very real effect, treatment with lowest prevalence is treatment (P4: 24%) with prevalence value 23,3% andhighestpervalence that is treatment (P5: 30%) with prevalence value equal to 40 %. In the synthesisofdumbo catfish with the giving of strychnine bush extract have a very real effect, the treatment with lowest stability is treatment (P4: 30%) with 77% syntax value and the highest synthesis of treatment (P5: 24%) with 90% syntax value. This study resulted in the conclusion that the best treatment for prevalence and survival rate is treatment (P4: 24%). As for the higher inhibition power dose strychnine bushextractis used then the higher the power inhibition.